5PSQ-111 Evaluation of the form's quality of medical prescriptions from public hospitals and private clinics. (March 2019) - Bennis, S; Alami Chentoufi, M; Ouhaddouch, H; Yachi, L; Cheikh, A; Bouatia, M
Abstract : Background: The medical prescription is the main document of communication between the doctor, the pharmacist and the patient. The careful writing of this document enables the reduction of many therapeutic errors. Purpose: The purpose of this work was to evaluate the quality of the form of medical prescriptions from public hospitals and private clinics. Material and methods: This was a transversal descriptive study of 210 medical orders. The quality of the form was evaluated using two parameters: the presence of the obligatory mentions and their legibility. An analysis grid with several items was used to collect the information needed to describe the form quality of the medicinal prescriptions. The pharmacist used a scale of 1 to 3 to evaluate the readability of prescriptions. Results: In our study, 210 patients were included taking a total of 588 drugs. 28.57% (60) medical prescriptions came from public hospitals, while 71.42% (150) prescriptions stemmed from private clinics. For all the medical prescriptions analysed, only 21 were computerised and came from private clinics. Only one medical prescription from a public hospital was undated. All prescriptions were written with commercial drug names. In the sample studied, 15.71% (33) prescriptions had no patient identity (first and last name) and came from public hospitals. Only six medical prescriptions contained the age and weight of the patient and came from private clinics. The identity of the prescribing physician was absent in 14.2% (30) medical prescriptions and 38.57% (81) medical prescriptions did not contain a treatment period. Among the medical prescriptions reviewed, 10% (21) were deemed illegible by the pharmacist, while 40% (84) were considered difficult to read. Conclusion: This study shows that prescriptions from public hospitals have serious incoherence compared to those from private clinics. This is due to the high number of patients who consult in public hospitals. This work has also demonstrated that hand-written medical orders give several non-compliance. The teaching of order-writing technique and its computerisation are required to improve the quality of medical prescribing. References and/or acknowledgements: Dr Mamouni Alaoui Faiçal. No conflict of interest.